Neonate Aortic Stenosis: Importance of Myocardial Perfusion in Prognosis - Santos,Marco Aurélio (2002)
OBJECTIVE: To analyze our experience with percutaneous aortic balloon valvuloplasty in newborn infants with aortic stenosis, emphasizing the extraordinary importance of myocardial perfusion.METHODS: Over a 10-year-period, 21 neonates underwent percutaneous aortic balloon valvuloplasty. Age ranged from 2 to 27 days, weight ranged from 2.2 to 4.1 kg and 19 were males. All patients presented with congestive heart failure that could not be treated clinically. The onset of symptoms in the first week of life occurred in 9 patients considered as having critical aortic stenosis. Severe aortic stenosis occurred in 12 patients with the onset of symptoms in the second week of life.RESULTS: Mortality reached 100% in the patients with critical aortic stenosis. The procedure was considered effective in the 12 patients with severe aortic stenosis. Vascular complications included the loss of pulse in 12 patients and rupture of the femoral artery in 2 patients. Cardiac complications included acute aortic regurgitation in 2 patients and myocardial perforation in one. In an 8.2±1.3-year follow-up, 5 of the 12 patients died (2 patients due to septicemia and 3 patients due to congestive heart failure). Five of the other 7 patients underwent a new procedure and 2 required surgery.CONCLUSION: Percutaneous aortic valvuloplasty in neonates is not an effective procedure in the 1st week of life, because at this age the common presentation is cardiogenic shock. It is possible that, in those patients with critical aortic stenosis, dilation of the aortic valve during fetal life may change the prognosis of its clinical outcome.